Physiological models to understand exercise fatigue and the adaptations that predict or enhance athletic performance - Noakes, T. D. (Scandinavian Journal of Medicine & Science in Sports, 2000)
A popular concept in the exercise sciences holds that fatigue develops during exercise of moderate to high intensity, when the capacity of the cardiorespiratory system to provide oxygen to the exercising muscles falls behind their demand inducing "anaerobic" metabolism. But this cardiovascular/anaerobic model is unsatisfactory because (i) a more rigorous analysis indicates that the first organ to be affected by anaerobiosis during maximal exercise would likely be the heart, not the skeletal muscles. This probability was fully appreciated by the pioneering exercise physiologists, A. V Hill, A. Bock and D. B. Dill, but has been systematically ignored by modern exercise physiologists; (ii) no study has yet definitely established the presence of either anaerobiosis, hypoxia or ischaemia in skeletal muscle during maximal exercise; (iii) the model is unable to explain why exercise terminates in a variety of conditions including prolonged exercise, exercise in the heat and at altitude, and in those with chronic diseases of the heart and lungs, without any evidence for skeletal muscle anaerobiosis, hypoxia or ischaemia, and before there is full activation of the total skeletal muscle mass, and (iv) cardiovascular and other measures believed to relate to skeletal muscle anaerobiosis, including the maximum oxygen consumption (VO2 max) and the "anaerobic threshold", are indifferent predictors of exercise capacity in athletes with similar abilities. This review considers four additional models that need to be considered when factors limiting either short duration, maximal or prolonged submaximal exercise are evaluated. These additional models are: (i) the energy supply/energy depletion model; (ii) the muscle power/muscle recruitment model; (iii) the biomechanical model and (iv) the psychological model. By reviewing features of these models, this review provides a broad overview of the physiological, metabolic and biomechanical factors that may limit exercise performance under different exercise conditions. A more complete understanding of fatigue during exercise, and the relevance of the adaptations that develop with training, requires that the potential relevance of each model to fatigue under different conditions of exercise must be considered. Scand J Med Sci Sports 2000 Jun;10(3):123-45